2023
DOI: 10.1039/d2lc00873d
|View full text |Cite
|
Sign up to set email alerts
|

Beyond biology: alternative uses of cantilever-based technologies

Abstract: Microcantilever-based platforms are presented as versatile lab-on-chip devices for advanced applications spanning from material characterization and environmental monitoring to energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 213 publications
0
7
0
Order By: Relevance
“…However, one underutilized technology for sensitive signal transduction includes the use of microcantilevers. 316 Microcantilevers have been attracting growing interest due to their low-cost batch fabrication methods, simple electronic integration, and versatile detection capabilities. Several examples of membrane-augmented cantilevers have been presented within the literature, whereby deformation of a silicon 317 or polyimide 318 membrane was used to deflect a cantilever either as a generalized pressure sensor or, in the latter case, to monitor pulse waves in healthcare settings.…”
Section: Membrane Applications Within Microfluidic Devicesmentioning
confidence: 99%
“…However, one underutilized technology for sensitive signal transduction includes the use of microcantilevers. 316 Microcantilevers have been attracting growing interest due to their low-cost batch fabrication methods, simple electronic integration, and versatile detection capabilities. Several examples of membrane-augmented cantilevers have been presented within the literature, whereby deformation of a silicon 317 or polyimide 318 membrane was used to deflect a cantilever either as a generalized pressure sensor or, in the latter case, to monitor pulse waves in healthcare settings.…”
Section: Membrane Applications Within Microfluidic Devicesmentioning
confidence: 99%
“…In this research, we investigated methods for identifying the compositions or weight fractions of thin-film amorphous alloys. We propose a novel approach utilizing micromechanical sensors (such as MEMS-based sensors), which have been extensively used in a wide range of applications across different fields owing to their small size, fast response, and high sensitivity, and ellipsometry to determine the compositions of binary Zr-Cu alloys [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…1 This is primarily attributed to the functionalization of the PD-MC surface with layers that bind target analytes, thereby allowing for precise detection and quantification of gases. 1 Several studies have been conducted to investigate the potential of PD-MC beams as gas sensors, and the results have been encouraging. For instance, Li et al demonstrated the use of an array of PD-MCs complemented by machine learning to detect and quantify different volatile organic compounds (VOCs) with graphene oxide (GO) functional layers.…”
mentioning
confidence: 99%
“…KEYWORDS: nonlinear dynamics, functionalization layer, Young's modulus, resonance frequency, gas sensing, low concentrations, response model P iezoelectrically driven microcantilever (PD-MC) beams have emerged as a promising platform for developing gas sensors 1−3 due to high levels of specificity and sensitivity. 1 This is primarily attributed to the functionalization of the PD-MC surface with layers that bind target analytes, thereby allowing for precise detection and quantification of gases. 1 Several studies have been conducted to investigate the potential of PD-MC beams as gas sensors, and the results have been encouraging.…”
mentioning
confidence: 99%
See 1 more Smart Citation